Testing the Construct Validity and Reliability of the Student Learning Motivation Scale Using Confirmatory Factor Analysis (CFA) - Gugun Gusmanida; Hironimus Sujati; Herwin Herwin (Postgraduate, University of Mataram, 2024)
Constructivist learning environments are created by utilizing constructivist theory to raise teaching standards and motivate students to learn more. The low level of student motivation in the learning process is caused by several problems that occur. Thus, learning motivation is very important in the progress of learning, namely to encourage enthusiasm during the learning process. This research aims to measure students' learning motivation. The sample for this research was fourth grade elementary school students. This research uses a quantitative approach designed using measuring instruments in the form of questionnaires. The results of the research show that these four aspects are: the desire and desire to succeed, the appreciation for learning, the desire to be interested in learning, and optimism. There is one indicator that does not meet the criteria, namely the reward aspect of learning. Therefore, the three aspects that have been described are proven to meet the criteria of goodness of fit, validity and construct reliability. Therefore, the scale developed is suitable for use in collecting data to measure student learning motivation.